2016
DOI: 10.1161/circulationaha.116.022603
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Prognostic Utility of Indexes of Microvascular Function Alone or in Combination in Patients With an Acute ST-Segment–Elevation Myocardial Infarction

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
120
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 153 publications
(126 citation statements)
references
References 61 publications
6
120
0
Order By: Relevance
“…Variables with a P <0.05 in univariable analysis and possible confounders of PWV were entered in a multivariable model together with PWV. As previously discussed, due to the limited number of MACCE events, a maximum of 2 variables were entered in each model 17. Together with presence of multivessel disease, PWV, age, mean blood pressure, NT‐proBNP concentrations, and LV stroke volume were used as dichotomized variables for outcome analysis to allow for an adequate comparison of hazard ratios.…”
Section: Methodsmentioning
confidence: 99%
“…Variables with a P <0.05 in univariable analysis and possible confounders of PWV were entered in a multivariable model together with PWV. As previously discussed, due to the limited number of MACCE events, a maximum of 2 variables were entered in each model 17. Together with presence of multivessel disease, PWV, age, mean blood pressure, NT‐proBNP concentrations, and LV stroke volume were used as dichotomized variables for outcome analysis to allow for an adequate comparison of hazard ratios.…”
Section: Methodsmentioning
confidence: 99%
“…We previously found that an IMR value of >27 was most closely associated with microvascular obstruction and myocardial hemorrhage, whereas an IMR >40 was most closely associated with all‐cause death or heart failure 13. We also observed that IMR was associated with the systemic concentration of IL‐6 on the first day post‐STEMI, reflecting systemic inflammation and vascular injury 13.…”
Section: Discussionmentioning
confidence: 78%
“…We previously found that an IMR value of >27 was most closely associated with microvascular obstruction and myocardial hemorrhage, whereas an IMR >40 was most closely associated with all‐cause death or heart failure 13. We also observed that IMR was associated with the systemic concentration of IL‐6 on the first day post‐STEMI, reflecting systemic inflammation and vascular injury 13. The current study extends these findings because a bimodal thermodilution waveform was associated with heart failure post–myocardial infarction, systemic inflammation (monocyte count), and circulating concentrations of NT‐proBNP early post–myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations